Implementasi Sistem Pengelolaan Aset Desa (SIPADES) di Kecamatan Bengkalis - Irma Safitri (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to evaluate the implementation of the Village Asset Management System (SIPADES) in Bengkalis Regency. The focus of the research was to assess the effectiveness of this system in helping village officials manage assets. The research was conducted in six villages using a descriptive qualitative method. Data collection was conducted through reduction, presentation and conclusion drawing. The results showed that villages in Bengkalis Regency had implemented SIPADES well. Village operators, although most of them were only high school graduates, were able to master SIPADES thanks to intensive training. However, the main obstacles are network limitations that cause system errors and downtime, disrupt operational efficiency and stability of village asset management, and make it difficult to track data in real-time. Overcoming these problems requires improved technology infrastructure and better support so that SIPADES can run smoothly and effectively in all villages.